Weathering resistance of solventborne polyurethane/nanosilica composite - Ching, Yern Chee; Ching, Yun Chen; Yaacob, Iskandar (American Scientific Publishers, 2012)
Hybrids containing nanosize inorganic/organic composite were prepared from solventborne polyurethane (PU) and nanosilica. The composite was prepared with addition of nanosilica contents range from 0 to 14 wt%. PU/nanosilica composite samples with 1 mm thickness were prepared. The accelerated weathering study was conducted by exposing the sample to ultraviolet radiation. Photooxidation of polyurethane and its composites induced by ultraviolet exposure after 200 hrs and 500 hrs was investigated. Infrared spectroscopy was used to monitor chemical changes that occurred upon photoageing. The changes of the mechanical and thermal stability properties of the UV-exposed PU/nanosilica composite materials were measured by universal tensile machine, DMA and TGA. The urethane linkage (C–NH) was very sensitive to UV radiation and the photooxidation increased with the increasing of UV exposure time. However, with the addition of 6 wt% nanosilica, PU/nanosilica-6% composite showed better weather resistant compared to the neat PU. There was less deterioration and only minor chemical changes was found on PU with addition of 6 wt% nansilica after as much as 500 hrs QUV weathering. However, the introduction of high amount of nanosilica up to 14 wt% contents will accelerate the photooxidation rate of PU. The weathering effect has increased the carbonyl containing product and caused the increase of tensile modulus of the sample. Simultaneously, the DMA measurement showed that the crosslink density of the PU/nanosilica composite decreased with increasing of photodegradation rate. These effects were more pronounced with 14 wt% nanoslica content.